Numerical Evaluation of Residual Stress Influence on SIF in CT Specimen - Remigijus Janulionis; Gintautas Dundulis (Applied Sciences, 2023)
Residual stresses are usually associated with stresses induced by heterogeneous deformations as a cause of phase transition and thermal stress. The residual stresses can appear during the manufacturing process, repair process, or in some cases due to operational loads. These stresses should be taken into account in the structural integrity evaluation of low-toughness materials or in the case of fatigue and/or stress corrosion cracking (SCC) situations. Indeed, it is known that residual stresses affect crack growth rates. For a better understanding of how these stresses can interact with crack propagation in pre-strained stainless-steel specimens, numerical modeling has been performed. The tension of the compact tension (CT) specimen was simulated and as a result, the stress intensity factor (SIF) was calculated. The main goal of this paper is to numerically calculate the stress intensity factors along the crack front of the CT specimen with residual stresses and compare them with the results of tension of the same specimen just without residual stresses. For this task finite element analysis (FEA), code CAST3M was used. Simulation results showed that the higher SIF values were calculated at the sides and the lower in the middle part of the CT specimen machined from a highly pre-strained plate which is opposite to what could be expected in a specimen without residual stresses.